Effect of B2O3 on reduction of FeO in Ti bearing blast furnace primary slag. (August 2015) - Ren, S.; Zhang, J. L.; Liu, Q. C.; Chen, M.; Ma, X. D.; Li, K. J.; Zhao, B. J.
<x content-type="archive" xml:space="preserve">Abstract</x> The effect of B2O3 on reduction of FeO from iron saturated FeO–CaO–SiO2–MgO–Al2O3–TiO2 slags by graphite has been studied under static conditions between 1473 and 1573 K. The compositions of quenched samples were determined by electron probe X-ray analysis (EPMA). The reduction degree (R) of FeO in each sample was obtained by mass balance and compared with the reduction of FeO in the slags without B2O3. The results showed that FeO reduction in the primary slag was effectively improved with only 1 mass-% B2O3 content, but did not continue to increase with the increase in B2O3 content and it reduced slightly at about 3 mass-%B2O3. After reduction B2O3 gathered in the liquid phase where it can restrain the formation of iron–titanium oxide and promote the reduction of FeO, so benefiting blast furnace operation.